Job Hiring Management System for H.I.S. Management Services - Muhammad Uzair Mohd Faizul,; Norhanim Selamat,; Marniza Jamalan, (Applied Information Technology And Computer Science, 2023)
Job Hiring Management System is a system that will help a company in hiring new employees. Based on the research conducted, the use of Microsoft Word, Microsoft Excel, Gmail and job search engines such as JobStreet are used for hiring. Using multiple software systems can cause delays in the hiring process as information relevant to the hiring process is scattered across different platforms. Moreover, relying solely on JobStreet services for only advertising purposes can be expensive. Therefore, this Job Hiring Management System was developed using web-based technology such as HTML, CSS, JavaScript, Vue.js, Node.js, Express, PostgreSQL and Redis that was designed via Multi-tier Architecture to facilitate access to managers, Human Resources officers and applicants throughout the hiring process. This can help improve the efficiency and effectiveness of Human Resources officers and managers during the hiring process by listing applicant feature for shortlisting and interview purposes. Furthermore, the existence of a centralized system can store all information related to the hiring process as well as reduce the cost of the company's expenses for the smoothness of the hiring process.